Les sanctions educatives : de l‘ambiguite persistante de la prise en charge du mineur délinquant - Didier Benoît (Sociétés et Jeunesses en Difficulté)
Educational penal “sanctions”: on the persistent ambiguity of social work with delinquent minors                            The aggravation of delinquency by minors seems to justify the intervention of the legislator. The increasingly young age of young delinquents together with their violent character has led our Law maker to reform the edict of 2nd February 1945, deemed by some to be too lax. Included among the new measures suggested in response to the behaviour of delinquency by minors are “educational sanctions”. Because these mix together the terms “sanction” and “education”, and until now sanction and educational measures were always considered to be exact opposites, this definition is evidently ambiguous. Some educational sanctions do not display any educational characteristics (for example, confiscating the article used to commit the offence), others cannot be considered sanctions (a course in civic education). Furthermore, an examination of their content reveals clauses that already exist, so there is nothing new in these measures. The originality of these sanctions is more to do with their symbolic and political value. Indeed, pressurised by public opinion, the legislator’s response has been political, rather than a response giving meaning to the content. All the difficulties of defining a coherent policy for dealing with delinquency still remain today.